APLIKASI MODEL S-O-R PADA ANALISIS PENGARUH E-WOM MELALUI SOCIAL MEDIA INFLUENCER, CELEBRITY ENDORSEMENT, DAN CUSTOMER REVIEW TERHADAP MINAT BELI DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi Kasus pada konsumen produk Erigo melalui S-commerce TikTok Shop) - Mukti, Khansania Adinda; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Technological developments impacted society to have new trends such as shopping for fashion products through the s-commerce platform, TikTok Shop. With this online shopping trend and the limitations felt by consumers because they cannot assess products directly and physically, E-WOM (Electronic Word-Of-Mouth) has become the main source of information for potential customers. That’s why E-WOM could be considered to hold such a prime effect on an online consumer’s perception, such as the perception of the brand image in a customer’s point of view. Also with the existing intense competition among the local fashion brand market, many companies are striving to utilize E-WOM as a marketing efforts in s-commerce to influence customer behavior, especially purchase intention. The intention to buy products remains a matter of debate because consumers' purchase intentions often change according to consumer behavior. As the ultimate goal of marketing is to help companies generate sales, the use of E-WOM in s-commerce should be considered by companies to form a brand image which can result in influencing consumers to foster buying interest. The purpose of this study is to determine and compare the influence of E-WOM in the form of Social Media Influencers, Celebrity Endorsements, and Customer Reviews on purchase intention and brand image as intervening variables to analyze its relationship with the S-O-R (Stimulus-Organism-Response) model theory on the case of Erigo through the TikTok Shop s-commerce. This research begins by applying a framework or research model that is S-O-R (Stimulus-Organism-Response). Furthermore, data was obtained from 135 respondents by distributing questionnaires via social media. Respondents are TikTok users in Indonesia who have known Erigo before. The data obtained was analyzed quantitatively and structurally using the Structural Equation Modeling (SEM) method using the Analysis Moment of Structural (AMOS) version 23 program. This study found that the three E-WOM communicants in the form of Social Media Influencers, Celebrity Endorsements, and Customer Reviews have a significant positive influence on Brand Image, as well as Brand Image has a significant positive influence on Purchase Intentions. Not only that, but the three E-WOM communicants (Social Media Influencers, Celebrity Endorsements, Customer Reviews) have also proven to have a direct influence on Purchase Intentions. It is hoped that the Managerial Implications of this research can be used as a suggestion for determining Erigo's marketing communication strategy through TikTok s-commerce